Empowering 21st-Century Learners: Enhancing Digital Literacy Through E-Literate Integration in Science Education - Rayendra; Jodi Hardika (Postgraduate, University of Mataram, 2026)
Digital literacy is a critical 21st-century competency that must be integrated into science education to achieve Sustainable Development Goal 4 (Quality Education). This study evaluates the effectiveness of the E-Literateapplication in enhancing students' digital literacy within the specific context of vibration and wave topics. Using a quasi-experimental pretest–posttest control group design, this research involved 60 grade VIII students divided into experimental and control groups. The research instrument utilized a performance-based digital literacy test (comprising case studies on information access, evaluation, processing, and digital ethics) to measure actual proficiency rather than mere self-perception. Data were analyzed using normalized gain (N-Gain), independent t-test, and Cohen’s effect size. The results indicated a significant difference in digital literacy improvement between the two groups (p < 0.05). The experimental group, which utilized the E-Literate app to simulate wave phenomena and verify digital information, achieved a very large effect size (d = 4.63). These findings demonstrate that the E-Literate application is not only an effective medium for mastering abstract science concepts like vibrations but also a powerful tool for bridging the digital skills gap in secondary education.